A New Kinetic Spectrophotometric Method for the Quantitation of Amorolfine - César Soto; Cristian Poza; David Contreras; Jorge Yáñez; Fallon Nacaratte; M. Inés Toral (Journal of Analytical Methods in Chemistry)
Amorolfine (AOF) is a compound with fungicide activity based on the dual inhibition of growth of the fungal cell membrane, the biosynthesis and accumulation of sterols, and the reduction of ergosterol. In this work a sensitive kinetic and spectrophotometric method for the AOF quantitation based on the AOF oxidation by means of KMnO4 at 30 min (fixed time), pH alkaline, and ionic strength controlled was developed. Measurements of changes in absorbance at 610 nm were used as criterion of the oxidation progress. In order to maximize the sensitivity, different experimental reaction parameters were carefully studied via factorial screening and optimized by multivariate method. The linearity, intraday, and interday assay precision and accuracy were determined. The absorbance-concentration plot corresponding to tap water spiked samples was rectilinear, over the range of 7.56 × 10−6–3.22 × 10−5 mol L−1, with detection and quantitation limits of 2.49 × 10−6 mol L−1 and 7.56 × 10−6 mol L−1, respectively. The proposed method was successfully validated for the application of the determination of the drug in the spiked tap water samples and the percentage recoveries were 94.0–105.0%. The method is simple and does not require expensive instruments or complicated extraction steps of the reaction product.